E-Court Implementation In Civil Cities Jurisdiction In The Covid-19 Pandemic Time - Hendra Purwanto Arifin; Angga Ferdian; Mochamad Djunaedi; Dewi Ika Agustina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
In this scientific paper report, it discusses the implementation of e-Court in civil court cases during the Covid-19 pandemic. There are still many parties who do not understand and see how e-Court is in a civil case. In the current digital era, the Supreme Court also supports government programs by minimizing direct contact, avoiding crowds, and using online or online media in court operations manifested in e-Court. Prior to the Covid-19 period, there were already several civil courts using e-Court, but not many cases were tried using the e-Court application so that the parties prefer to hear conventionally. With this pandemic period, it is hoped that the Supreme Court will further encourage the litigant to use e-Court so that the rights of the people to seek justice can still be fulfilled despite the conditions of the Covid-19 pandemic. Because the e-Court application is a program that utilizes technology applications, the Supreme Court should provide education and outreach to judges, court staff, advocates, and the general public regarding and procedures for proceeding with civil cases by e-Court.